2011
DOI: 10.1007/s10265-010-0400-z
|View full text |Cite
|
Sign up to set email alerts
|

Selective embryo abortion in a perennial tree-legume: a case for maternal advantage of reduced seed number per fruit

Abstract: In this study, I analyzed time-course of embryo abortion, positional bias in seed maturation and maternal costs of seed packaging in Cercis canadensis. While basal embryos experience similar rates of abortion as those in other positions during the first week of development, abortion rates peak during the second week. Head start in resource sequestration by stigmatic embryos may explain high rates of basal embryo abortion. Similar seed packaging costs and seed mass for single and multi-seeded pods suggests that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…From an evolutionary perspective, the advantage of overproduction of ovaries relative to the number of seeds set could be explained by (i) a ‘bet-hedging’ strategy in which plants could quickly adjust the number of seeds in response to unpredictable environments ( Lloyd, 1980 ; Kozlowski and Stearns, 1989 ; Burd, 1998 ; Arathi, 2011 ) and (ii) a mechanism for eliminating ovaries of low quality and survival probability, in order to efficiently invest resources in more competitive ovaries ( de Jong and Klinkhamer, 2005 ; Mena-Ali and Rocha, 2005 ; Arathi, 2011 ), especially when resources are deficient, for example, under abiotic stresses ( Ruan, 2014 ; Tardieu et al , 2014 ). This hypothesis predicts that kernel set or abortion closely relates to the amount of resources available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From an evolutionary perspective, the advantage of overproduction of ovaries relative to the number of seeds set could be explained by (i) a ‘bet-hedging’ strategy in which plants could quickly adjust the number of seeds in response to unpredictable environments ( Lloyd, 1980 ; Kozlowski and Stearns, 1989 ; Burd, 1998 ; Arathi, 2011 ) and (ii) a mechanism for eliminating ovaries of low quality and survival probability, in order to efficiently invest resources in more competitive ovaries ( de Jong and Klinkhamer, 2005 ; Mena-Ali and Rocha, 2005 ; Arathi, 2011 ), especially when resources are deficient, for example, under abiotic stresses ( Ruan, 2014 ; Tardieu et al , 2014 ). This hypothesis predicts that kernel set or abortion closely relates to the amount of resources available.…”
Section: Discussionmentioning
confidence: 99%
“…However, pollen limitation is not a common occurrence in many angiosperms ( Bawa and Webb, 1984 ; Burd, 1994 ; Larson and Barrett, 2000 ; Sakai and Harada, 2001 ). Instead, post-fertilization seed abortion can frequently be induced due to limitations in the available resources ( Snow and Spira, 1991 ; Arathi et al , 1999 ; Yang et al , 2005 ; Brookes et al , 2008 ; Arathi, 2011 ), and it can become more severe under unfavorable circumstances, including drought ( Otegui et al , 1995 ; Andersen et al , 2002 ; McLaughlin and Boyer, 2004a, b ), heat ( Cheikh and Jones, 1994 ; Hays et al , 2007 ; Liu et al 2016 ), and other environmental stresses ( Andrade et al , 2002 ; Hiyane et al , 2010 ). Given the increased frequency and severity of climate-change-related stresses, seed abortion has become a central issue for food security in the 21st century ( Grassini et al , 2013 ; Ray et al , 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is a common law that angiosperms produce more ovaries than final seeds, which results in unavoidable selective ovary abortion (Stephenson, 1981;Ruan et al, 2012). Evolutionarily, overproduction of ovary allows plants (a) to quickly adjust the seed number in response to an unpredictable environment (Lloyd, 1980;Kozlowski & Stearns, 1989) and (b) to efficiently invest limited resources in more competitive progenies (de Jong & Klinkhamer, 2005;Mena-Ali & Rocha, 2005;Arathi, 2011). In this study, we demonstrated that a short-term postpollination drought induced irreversible abortion of apical kernels even if sufficient irrigation was subsequently applied (Figure 3).…”
Section: Competition For Assimilates That Is Exacerbated By Droughtmentioning
confidence: 99%
“…Here, weak sink effects may be underlying the lower fruit set rates during times of presumably unlimited resources and may be further exacerbated by low flowering intensity during the earlier pollination weeks. When flowering intensity is low, increased pollination intensity appears advantageous to fruit set, possibly by establishing a stronger resource sink (e.g., an increased number of developing cherelles) driving the internal plant physiological processes (i.e., assimilate production and/or remobilization, hormone production) that support the fertilization success of subsequently pollinated flowers (Arathi, 2011).…”
Section: Discussionmentioning
confidence: 99%